PENGARUH INPUT PROSES RELATIONSHIP MARKETING TERHADAP OUTPUT PROSES RELATIONSHIP MARKETING STUDI KASUS GRAND INNA MALIOBORO HOTEL & CONVENTION - Surawan Setya Budi S (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2019)
This research use relationship marketing teory which applied 4 factor of input process understanding customer expectations, building service partnerships, empowiring employers, and total quality management, and output relationship marketing process: customer satisfaction and customer layalty. The objective of this research is to find out wich factors of input process that has more impact on the output process in relationship marketing. There are 60 trusted correspondencea from Grand Inna Malioboro Hotel customer whom at least have been stayed at the hotel three times. The method of collecting data in these research use questioners and Likert scale measuring instrument 5 points that will be tested by the instrument and analyzed by using regressision analysi the simultaneous test of variabel for the relationship marketing input s. The result of the instrument shows the items used are valid and reliable. It displays the outpout process passed the assumtions test, while the signifikacant relationship marketingto the output of relationtionship marketing, For the passive test of vareable input process relationship marketing with the ouput process relationship marketing shows all significant variables unless vareabel understands customer expectations does not have a significant effect on the process of output relationship marketing.